Environmental Chemistry Modules Development to Enhance Students' Creative Thinking Abilities in Heavy Metal Water Pollution Materials - Hadi Apriyoanda; Agus Sundaryono; M. Lutfi Firdaus (PendIPA Journal of Science Education, 2020)
Development of teaching material based on laboratory research is one way that can be done to improve students' creative thinking abilities in meeting the challenges of 21st century learning. The aims of this study are to determine the feasibility of the developed environmental chemistry modules, to improve of students' thinking abilities and determine the students’ responses to the use of modules in environmental chemistry lectures. Module development by R and D methods 4D model, namely Define, Design, Develop and Disseminate. Module quality is determined by expert validation test. Based on the results of expert validation, the module developed obtained 90.91% percentage of eligibility with a very good category. Based on the N-Gain value obtained, an increase in students' creative thinking abilities on the aspect of  flexibility was 0.47, and the aspect of elaboration was 0.64 with medium category. The student responses to the use of modules in learning enviromental chemistry obtained a percentage of 83.82% with very good category.